Answer:
D)
![(1)/(6)](https://img.qammunity.org/2022/formulas/mathematics/college/gpc1ak4i9759keh7exqfjuy6nrxj1gkyt6.png)
g¹(1) =
![(1)/(6)](https://img.qammunity.org/2022/formulas/mathematics/college/gpc1ak4i9759keh7exqfjuy6nrxj1gkyt6.png)
The inverse of the function
![g(x) = \frac{x^{(1)/(3) }-1 }{2}](https://img.qammunity.org/2022/formulas/mathematics/college/hxv2a75ypfo2epqfio1qs88hd4p1ijuwtt.png)
Explanation:
Step(i):-
Given that f(x) = (2x+1)³
Let y = (2x+1)³
![y^{(1)/(3) } =2x+1](https://img.qammunity.org/2022/formulas/mathematics/college/9og64cdp43ue18cjscvz8rg27fwa17d76f.png)
![2x = y^{(1)/(3) } -1](https://img.qammunity.org/2022/formulas/mathematics/college/iyyyuf7hlfkxt42juhhseqr6h4wadl3gi1.png)
![x = \frac{y^{(1)/(3) }-1 }{2}](https://img.qammunity.org/2022/formulas/mathematics/college/azx9u9wnhdrxbqmzzsbk710fqus57xuuz0.png)
Step(ii):-
y = f(x) ⇒ x = f⁻¹ (y)
⇒
![f^(-1) (y) = \frac{y^{(1)/(3) }-1 }{2}](https://img.qammunity.org/2022/formulas/mathematics/college/pp3k3ooho3u0mx3qov699ilk8c8ufd90fh.png)
![f^(-1) (x) = \frac{x^{(1)/(3) }-1 }{2}](https://img.qammunity.org/2022/formulas/mathematics/college/w59vucv5dar4a423kgbdee1ah3lpl4k9jz.png)
The inverse of the given function
![g(x) = \frac{x^{(1)/(3) }-1 }{2}](https://img.qammunity.org/2022/formulas/mathematics/college/hxv2a75ypfo2epqfio1qs88hd4p1ijuwtt.png)
Differentiating equation (i) with respective to 'x', we get
![g^(l) (x) = (1)/(2) X (1)/(3) x^{(1)/(3) -1}](https://img.qammunity.org/2022/formulas/mathematics/college/c0ete77ehlatf6a0ljnesjgpjyucxt0pa7.png)
![g^(l) (x) = (1)/(6) x^{(-2)/(3) }](https://img.qammunity.org/2022/formulas/mathematics/college/r8bvgdc1d8yus6wcnac23yufx3dtmmgjdx.png)
Final answer:-
Put x=1
![g^(l) (1) = (1)/(6) 1^{(-2)/(3) } = (1)/(6)](https://img.qammunity.org/2022/formulas/mathematics/college/2tv99hw94vng39gg5c98ql0jx0a4r5z8bm.png)